Estudo de parâmetros toxicológicos em animais tratados com própolis e geoprópolis de abelhas nativas do Maranhão - ARAÚJO, Maria José Abigail Mendes (2009)
Propolis of Scaptotrigona aff. postica is popularly used in Maranhão State, Brazil, for treating wounds and respiratory illnesses. Nevertheless little is known about the possible adverse effects its usage. This study evaluated the acute and subchronic toxicity of propolis hydroalcoholic extract (PHE) from S. aff. postica. In the study 96 Swiss mice (males and females) were used, half to evaluate the acute toxicity and half for subchronic toxicity. In acute toxicity, the animals received oral single doses of PHE in concentrations of 1000, 2000 or 4000 mg/kg and were observed for 14 days. For subchronic toxicity evaluation, the mice received daily PHE during 15 days in concentrations of 100, 200 or 400 mg/kg. The animals were sacrificed and blood and organs were removed for biochemical, hematological and histopathology evaluation. The PHE did not induce death and the acute treatment significantly reduced serum concentrations of alanine aminotransferase and alkaline phosphatase, while the subchronic treatment significantly reduced aspartate aminotransferase concentration and increased triglycerides only in the male mice. In the liver s histopathological analysis it was observed slight leucocytes infiltration in the mice groups that received higher doses and slight steatosis in the subchronic treatment. Data indicate that the propolis hydroalcoholic extract (PHE) from S. aff. postica has low toxicity when used orally, even in high doses and in subchronic treatments.